Motivation in Games: A Literature Review - Felicia, P. (International Journal of Computer Science in Sport, 2012)
This paper explains why and how video games can motivate students to learn. It explains key concepts linked to motivation, engagement and flow, and illustrates how some features in video games can promote intrinsic motivation, hence encourage and sustain learning. In the second part of the paper, empirical evidence of the motivational aspects of video games is presented, with reference to recent scientific studies conducted essentially between 2005 and 2011. Evidence collected demonstrates that games are employed to increase learners' motivation, in a wide range of settings, for different topics (e.g., science, literature, or engineering), and to address the different needs and specificities of learners (e.g., gender, age, or special needs). It also shows that games can teach both academic and non-academic skills, and motivate students to collaborate, share information, and increase their attainments, and that, in many cases, they are more effective than traditional approaches. These results emphasize that some additional mechanisms need to be implemented in games to ensure that they systematically manage to engage, teach and change students behaviors. These include game design (e.g., personalized strategies, adapted challenge or a good balance between educational and entertaining features), and teaching strategies (e.g., briefing, debriefing, and teachers' support).